Efficacy and safety of daclatasvir plus asunaprevir therapy for chronic hepatitis C patients with renal dysfunction. Issue 4 (24th October 2016) - Nakamura, Yuki; Imamura, Michio; Kawakami, Yoshiiku; Teraoka, Yuji; Daijo, Kana; Honda, Fumi; Morio, Kei; Kobayashi, Tomoki; Nakahara, Takashi; Nagaoki, Yuko; Kawaoka, Tomokazu; Tsuge, Masataka; et al.
Abstract : Chronic hepatitis C virus (HCV) infection is associated with renal dysfunction. Daclatasvir and asunaprevir combination therapy showed a high virological response for genotype 1 chronic HCV‐infected patients with renal dysfunction on hemodialysis. However, the safety and efficacy of the therapy for patients with renal dysfunction who are not on hemodialysis are not well‐known. In total, 147 patients with chronic HCV genotype 1 infection were treated with 24 weeks of daclatasvir plus asunaprevir therapy. Among these patients, 126 had normal renal function (estimated glomerular filtration rate [eGFR] ≥ 50 ml/min/1.73 m 2 ) and 21 had renal dysfunction (eGFR < 50 ml/min/1.73 m 2 ). Plasma concentrations of daclatasvir and asunaprevir after 5 days of treatment were the same in the normal renal function and renal dysfunction groups. Early virological response (4, 8, 48, 96, and 168 hr after the start of the therapy) was similar between the two groups. End‐of‐treatment response was achieved in 122 (96.8%) and 20 (95.2%) patients with normal renal function and with renal dysfunction, respectively, and sustained virological response was achieved in 119 (94.4%) and 20 (95.2%) patients. The frequency of adverse events was also comparable between the two groups. Treatment discontinuation due to adverse events was required for only one patient in each group. Renal function did not change either during or after treatment in both groups. In conclusion, renal function is unlikely to have a significant impact on blood kinetics of daclatasvir and asunaprevir. This combination therapy was effective and safe for patients without hemodialysis. J. Med. Virol. 89:665–671, 2017 . © 2016 Wiley Periodicals, Inc.